ANALYSIS OF MOTOR PROFICIENCY BETWEEN URBAN AND RURAL CHILDREN - Janardhana, Varanasi; S. Sethu; Manikandan, P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the study was to analyse the Motor Proficiency between Urban and Rural Children. For this purpose, sixty (n=60) children were selected from Vivekananda Vidyashram Matriculation Higher Secondary School, Vannarpettai, Tirunelveli, Tamil Nadu, India and The Punjayat Union Primary School, Thenpathu, Tirunelveli, Tamil Nadu, India during the academic year 2017 - 2018. The subjects‟ age ranged between 6 to 8 years. The selected subjects were divided into two groups of thirty subjects each namely urban and rural children. The motor proficiency variables selected for this study are running ability, sliding ability, leaping ability, stationary dribbling ability, catching ability and kicking ability. The selected motor proficiency variables were assessed by using the standardized test manual (TGMD-2). The collected data on the selected variables were treated with independent „t‟ test 0.05 level of confidence. The results of the study indicates that the motor proficiency of rural children had registered significant level of difference on running ability, sliding ability, leaping ability, stationary dribbling ability, catching ability and kicking ability when compared to the urban children.